A variação fonético-fonológica nos anos finais do ensino fundamental : a monotongação dos ditongos decrescentes - Hasperoy, Renée de Souza (2021)
This study aims to analyze the beliefs and attitudes of teachers in the final years of Elementary School regarding sociolinguistic variation, specifically that of a phonetic-phonological nature. Therefore, we started with the theoretical assumptions of Sociolinguistics, specifically the variationist studies by Cabreira (1996), Toledo (2011) and Silveira (2019) on the monophthogization of the descending diphthong, as in bejo for beijo, caxa for caixa and ovido for ouvido, carried out in the light of the Theory of Variation (LABOV, 2008 [1972]) and from VARSUL speech database, and studies on Linguistic Beliefs and Attitudes (BALTHAZAR; CARRARO; LOREGIAN PENKAL, 2018; BOTASSINI, 2013). Nine teachers working in public and private schools in Porto Alegre-RS and the Metropolitan Region participated in this research. The research instruments used were a questionnaire, answered by the participants through the Qualtrics platform, and a list of questions, presented to the teachers in interviews carried out through Zoom Cloud Meetings. The answers to the two dissertation questions of the questionnaire and the interview questions were analyzed through the Content Analysis (BARDIN, 1977). The analysis of the responses to the questionnaire revealed that, although the teachers believe that sociolinguistic variation is important, this belief does not seem to support their teaching practices. In addition, issues related to Phonology were rarely addressed by the teachers, in opposition to Syntax, which was mostly mentioned. The analysis of the responses obtained through interviews, from which we sought to identify their knowledge about monophthongization conditioners, revealed a perception of the influence of the voiceless palato-alveolar fricative in contexts following diphthongs, a result that is in line with what was pointed out in Cabreira's research. (1996), Toledo (2011) and Silveira (2019). Considering that the other conditioners pointed out by these studies were not listed in the same measure, we found that the results of research referring to phonetic-phonological variation do not reach these teachers and, therefore, do not permeate their teaching practices.